Античное поселение «Приморский бульвар». Итоги исследований и проблема хронологии - Буйских, А.В.; Редина, Е.Ф. (Материалы по археологии Северного Причерноморья, 2015)
Our paper treats results of investigations on an ancient settlement situated in the centre of modern Odessa. A review of plain tableware, found at Prymorsky boulevard, revealed that it was produced since Late Archaic till Late Hellenistic periods, mostly in Olbia. This fact is a proof that the settlement was involved in the economic zone of Olbia since its very foundation.